Ecological risk management procedures - Dołęga, Marta; Biernat, Krzysztof (Studia Ecologiae et Bioethicae, 2009)
Risk management relies on identification, estimation, control and finance of potential risks. Excient process of management against alternate of ecological threat it’s people and nature resources protection before threats related to pollution of water, air, soil and other components of environment, which balance has been broken by reason of pronouncement of unexpected natural phenomenon, industrial failure and human activities. Negative environmental results are caused in case of pronouncement of threat damage to environmental component pollutions and ecosystems changes.